Exploring Cultural Identity and Nostalgia in South Asian Diasporic Literature (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The intricate relationship between cultural identity, nostalgia, and diasporic awareness in South Asian diasporic literature is examined in this essay.  It looks at how authors express the cultural, psychological, and emotional compromises people make while juggling their lives in their native country and their new one.  The study emphasizes issues like memory, displacement, hybridity, belonging, and generational identity transitions via in-depth readings of chosen literary works.  The research highlights how nostalgia may be used to both reimagine cultural continuity in diasporic areas and act as a connection to the past.  The study also explores how intergenerational tales, language, food, and rituals become symbolic markers of identity development.  The research highlights how South Asian diasporic authors describe identity as flexible, adaptable, and always changing, challenging fixed cultural borders by emphasizing the dynamic nature of cultural identity development.  In the end, this study advances our knowledge of how diasporic literature serves as a forum for resolving fractured histories and reaffirming cultural rootedness in cross-border settings.